Online Sex-Seeking Among Men who have Sex with Men in Nigeria: Implications for Online Intervention. - Stahlman, Shauna; Nowak, Rebecca; Liu, Hongjie; Crowell, Trevor; Ketende, Sosthenes; Blattner, William; Charurat, Manhattan; Baral, Stefan (AIDS & Behavior, 2017)
The TRUST/RV368 project was undertaken to apply innovative strategies to engage Nigerian MSM into HIV care. In this analysis we evaluate characteristics of online sex-seekers from the TRUST/RV368 cohort of 1370 MSM in Abuja and Lagos. Logistic regression and generalized estimating equation models were used to assess associations with online sex-seeking. Online sex-seeking (n = 843, 61.5 %) was associated with participation in MSM community activities, larger social and sexual networks, and higher levels of sexual behavior stigma. In addition, online sex-seeking was associated with testing positive for HIV at a follow-up visit [adjusted odds ratio (aOR) = 2.02, 95 % confidence interval (CI) = 1.37, 2.98)] among those who were unaware of or not living with HIV at baseline. Across visits, online sex-seekers were marginally more likely to test positive for chlamydia/gonorrhea (aOR 1.28, 95 % CI 0.99, 1.64). Online sex-seekers in Nigeria are at increased risk for HIV/STIs but may not be benefiting from Internet-based risk reduction opportunities.